Keli Frozen Fydaqueen: case study: company analysis / Addina Syaza Abdul Aziz … [et al.] - Abdul Aziz, Addina Syaza; Azmir, Fariesha Syazwani; Mohd Zaki, Muhammad Hafiz; Shaharin, Nur Annisa; Mohd Zurimi, Salmiza Ainatasya (2021)
For assignment purposes, a case study is done on small businesses to provide greater exposure to students in entrepreneurship. Therefore, we did a case study on a small business – Keli Frozen Fydaqueen. The business is a family-owned business that was founded in June 2020 by Puan Rafidah Binti Mohd Noor. We had followed the proper procedures and discussed the date and time with Puan Rafidah about the interview through an online WhatsApp call. We interviewed Puan Rafidah on the evening of 7 November 2021. We had gathered as much information as possible to complete the report on the case study. We put together the information and constructed a business model canvas that consists of customer segments, value proposition, distribution channel, customer relationship, revenue stream, key activities, key resources, key partners, and cost structure. From the interview, we also get to know the weaknesses of Keli Frozen Fydaqueen. The business has limited market coverage, weak advertising, and unsuitable property used to conduct the business. Hence, we included some solutions in the report for each of the problems, hoping that it will help Keli Frozen Fydaqueen to operate a better performance.